IN MEMORIAM - Quintanilla Cóndor, Cerapio (2021)
The task entrusted to me is a difficult one, because it involves much consternation and deep reflection. It is difficult because I must say goodbye, on behalf of all of us, to a very dear and respected friend who was a member of Quintaesencia magazine. It is, because I am overcome with pain, I am overcome with the nostalgia of losing a co-worker. Today is a sad day, a very sad day that takes us to unforgettable memories, accompanied by pleasant and very meaningful moments; to tell the truth: we feel the absence of a loved one. We regret the sudden departure of Dr. Humberto Guillermo Garayar Tasayco, due to COVID-19, a young, dynamic, enthusiastic and committed professor. It is very difficult to accept the fatal outcome of our friend; therefore, we are forced to share the despair, to support us in the pain, and pay a just compliment to Dr. Humberto.